Bond strength of surface-treated novel high translucent zirconia to enamel - Martin Ågren; Wen Kou; Margareta Molin Thorén (Medical Journals Sweden, 2019)
Aim: The aim of the present study was to evaluate the shear bond strength of zirconia, stabilised with 5% yttria, luted to enamel and to evaluate the fracture pattern at loss of retention. Methods: A total of 53 test specimen were manufactured from two partially stabilised zirconia materials, Zirkonzahn Prettau Anterior (ZPA) (n = 16) and Whitepeaks CopraSmile Symphony 5 layer (WCS) (n = 18), and a lithium disilicate (Ivoclar e.Max Press) (n = 19) acting as control. All test specimens were cemented to human enamel with Variolink Esthetic DC and then subjected to a shear bond strength test. Fracture and surface analysis were performed using light and scanning electron microscope. Results: No significant differences in shear bond strength were detected when analysing the three groups. Dividing them according to the fracture pattern significant difference in shear bond strength between the two zirconia groups could be seen analysing test bodies with failure of adhesion to the test body, but not to enamel. The ZPA had higher shear bond strength (23.68 MPa) than WCS (13.00 MPa). No significant differences were seen compared to the control group (19.02 MPa). Conclusion: Partially stabilised zirconia shows potential as a material to be used where macro mechanical bonding is not possible, although this study does not reveal how or if the bonding deteriorates over time.